Analisis Manajemen Risiko Pada Proyek Konstruksi Rehabilitasi Daerah Irigasi Bungkal Kota Sungai Penuh - Irman, Deni; Sulaeman, Agus (Universitas Batanghari Jambi, 2024)
In implementing construction projects, various obstacles arise from risks which cause the expected quality of work results to not be achieved, therefore it is necessary to implement risk management before implementing the Bungkal Irrigation Area construction project. The risk management used in this research is according to Australia/New Zealand. Standards (1999), risk management is part of a systematic process of identifying, analyzing, evaluating, controlling, supervising and communicating risks related to all activities, functions or processes with the aim of the company being able to minimize losses and maximize opportunities. The implementation of this risk management helps companies identify risks from the start and helps make decisions to overcome these risks. The aim of this thesis research is to identify risks in the rehabilitation of the Bungkal Irrigation Area in Sungai Full City before project implementation, so that they can find out how to control risks. This is to reduce losses that may arise from the risks of this rehabilitation construction activity. This research uses quantitative descriptive methods with interview methods and distributing questionnaires to respondents. The results of this research show that there are 3 risks that fall into the Extreme Risk category out of 32 existing risk indicators, namely: Flooding, first place, lack of depth of normalized soil excavation in irrigation drainage channels, second place, lack of supervision over work implementation, third place. Extreme risk is a risk that requires immediate treatment to reduce the risk, activities must not be carried out or continued. If risks cannot be reduced with limited resources, then the work cannot be completed.